Association between the Fatty Liver Index (FLI) and incident coronary heart disease: insights from a cohort study on the Chinese population - Miao, Ying; Wang, Yu; Yan, Pijun; Li, Yi; Chen, Zhuang; Tong, Nanwei; Wan, Qin (Frontiers in Endocrinology, 2024)
Background: The debate persists regarding whether metabolic dysfunction-associated steatotic liver disease (MASLD) actively contributes to coronary heart disease or merely acts as a passive indicator.Objective: This research aims to clarify the relationship between liver fat accumulation, as quantified by FLI, and the risk of developing coronary heart disease. Methods: Conducted from April to November 2011, the REACTION project, spearheaded by the Endocrinology Branch of the Chinese Medical Association, focused on Chinese adults aged 40 and above. Comprehensive data collection employed both questionnaires and specialized medical equipment, covering physical measurements, blood pressure, and pertinent biochemical markers. The study population excluded those with pre-existing coronary heart disease and acute myocardial infarction. Based on the initial data, participants were segmented and grouped into three categories. Analytically, the study utilized Cox proportional hazards models, further enhanced by stratified analyses to identify variations within predefined demographic groups.In this study, we enrolled 8,647 participants, comprising 2,887 males and 5,760 females. Over the 10-year non-interventional follow-up period, 433 participants (5%) passed away due to various reasons, with 55 deaths attributed to coronary heart disease/myocardial infarction, accounting for 12.7% of total deaths. Additionally, 484 participants were diagnosed with new-onset coronary heart disease, resulting in an incidence rate of 5.5%. Spearman correlation analysis revealed a positive correlation between FLI and traditional risk factors for coronary heart disease, including age, male gender, abnormal glucose metabolism, hypertension, smoking, TG, TC, LDL-C, etc. The Log-rank test indicated a rising cumulative incidence of coronary heart disease with increasing FLI groupings (P<0.01). Moreover, Cox regression analysis highlighted a notable correlation between FLI levels as a risk factor and the onset of coronary heart disease. After adjusting for other risk factors, individuals in the 30≤FLI<60 group exhibited a 1.203-fold higher risk of coronary heart disease compared to those in the FLI<30 group (p=0.126), while participants in the FLI≥60 group had a 1.386-fold higher risk than those in the FLI<30 group (p=0.041). Conclusion: Elevated FLI values are strongly associated with an increased susceptibility to coronary heart disease, indicating its potential value as a prognostic marker for the condition.